Comportamiento agronómico de la cebolla roja (Allium cepa L), con diferentes niveles de abonos orgánicos, en el centro experimental la playita, cantón La Maná, 2014 - Vera Basurto, John Javier (2015)
This research was conducted in the Canton La Manà, Cotopaxi Province, in the La Playita, the extension of the Technical University of Cotopaxi. For this research was estimated a time of 120 days from planting to harvest, but the harvest at 90 days was ahead, because the plant acquired its absolute maturity, manifesting it by the bending of the leaves and the flattens the fruit. Block design was used completely random (DBCA) with 7 treatments and four repetitions each treatment; Compost research topic was, worm castings or vermicompost and water hyacinth or Dunger. Compost best answer was the vermicompost. By soil analysis it was found that the soil in this area is too poor in nutrients and topsoil is scarce too, since previously was causing river. The area is good as far as light is concerned, the same as presented, long periods of light, which favored the advancement and determined at harvest. The treatment, better said, as far as production is concerned, was treatment 3 (5 kg. Of vermicompost) .not to be so in their agronomic performance. Therefore the above hypothesis is rejected, and which reads "The treatment with 5 kg. Vermicompost will be the level to improve the agronomic performance in the cultivation of red onion on the Experimental Center "La Playita 'in La Maná Canton, 2014